Reactivity and Magnetic Coupling of Triangulene Dimers Linked via para-Biphenyl Units - Pérez-Elvira, Elena; Lozano, Marco; Huang, Qiang; Ma, Ji; Gallardo, Aurelio; Barragán, Ana; Lauwaet, Koen; Gallego, José M; Miranda, Rodolfo; Jelínek, Pavel; Écija, David; Soler-Polo, Diego; et al. (Angewandte Chemie (International ed. in English), 2025)
Triangulene and its homologues are promising building blocks for high-spin low-dimensional networks with long-range magnetic order. Despite the recent progress in the synthesis and characterization of coupled triangulenes, key parameters such as the number of organic linking units or their dihedral angles remain scarce, making further studies crucial for an essential understanding of their implications. Here, we investigate the synthesis and reactivity of two triangulene dimers linked by two (Dimer 1) or one (Dimer 2) para-biphenyl units, respectively, on a metal surface in an ultra-high vacuum environment. First-principles calculations and model Hamiltonians reveal how spin excitation and radical character depend on the rotation of the para-biphenyl units. Comprehensive scanning tunneling microscopy (STM) in combination with density functional theory (DFT) calculations confirm the successful formation of Dimer 1 on Au(111). Non-contact atomic force microscopy (nc-AFM) measurements resolve the twisted conformation of the linking para-biphenyl units for Dimer 1. On the contrary, the inherent flexibility of Dimer 2 induces the planarization of the para-biphenyl, resulting in the spontaneous formation of two additional five-membered rings per dimer connected by a single C-C bond (Dimers 2'). Furthermore, scanning tunneling spectroscopy (STS) measurements confirm the antiferromagnetic (S=0) coupling of the observed dimers, underscoring the critical influence of dihedral angles and structural flexibility of the linking units in π-electron magnetic nanostructures.
Keywords: open-shell character; scanning tunneling microscopy; π-electron magnetism; triangulenes; surface chemistry